Edukasi Pembuatan Yogurt Susu Kambing Sebagai Upaya Peningkatan Minat Berwirausaha Pada Ibu PKK Kalidami, Mojo, Gubeng, Surabaya - Endah Budi Permana Putri; Rizki Nurmalya Kardina; Youwan Tobing Lukiyono; Handayani Handayani (Wisanggeni : Jurnal Pengabdian Masyarakat, 2022)
The impact of the prolonged Covid-19 pandemic is that it is difficult to find work, there are layoffs, and it is difficult to meet daily needs. The source of income for Kalidami residents is still centered on the husband's income, so housewives also need to have skills so that income does not only come from their husbands. The purpose of this community service activity is to increase knowledge of making goat's milk yogurt and interest in entrepreneurship for PKK RT 05, Kalidami, Mojo, Gubeng, Surabaya. A total of 15 PKK RT 05 Kalidami mothers were given education using lecture and question and answer methods. The media used are videos and booklets. The evaluation was carried out by giving a knowledge questionnaire about yogurt making with a maximum total score of 5 points, followed by statistical analysis using the Paired Sample Test. The result of this activity is that there is a significant increase in knowledge (p-value 0.00) in the target group of PKK women RT05 Kalidami indicated by the average score of knowledge about yogurt before being given education of 2.07 and after being given education it increased to 4 ,40. Education on making goat's milk yogurt with video media and booklets is effective in increasing knowledge and interest in entrepreneurship among PKK women in RT 05 Kalidami, Mojo, Gubeng, Surabaya.